More than a catchword: Taking lingustic diversity seriously - Gąsiorowski, Piotr (Wydział Anglistyki, Uniwersytet im. Adama Mickiewicza w Poznaniu, 2025)
The role of linguistic diversity and its importance for the "health" of linguistic ecosystems is discussed in the light of insights drawn from evolutionary biology and provided by the theory of complex adaptive systems.